Action Plan for Neighborhood Arrangement of Ubud Area Traditional/Historic Settlements in Gianyar Regency - I Wayan Gede Sularsa Budi Putra Jaya; I Wayan Parwata; Agus Kurniawan (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: The shift in the value of tradition/history impacts the structure of the built neighbourhood, such as changes in the residential area. It is both in terms of the environment and the building. Design/methodology/approach: This research is based on qualitative research. Findings: The historical value of a place/region is closely related to the traditional aspects that already exist and developed in that areaa. Every effort to preserve historical values and formal existence in a fostered neighbourhood does not impede economic develompent. Instead, they must be able to synergize, support each other, and be in line without sacrifing one or the other. It must also create a strong bond in development. So the conservation aspects is very relevant to be preserved in developing a fostered neighbourhood. Research limitations/imlications: The negative impact of ignorring more essential values on development can reduce the number or historic buildings and areas in most cities in Indonesia from year to year. As a results, development activities oriented towards economic growth can gradually eliminate historical traces, including a built neighbourhood. Practical implications: A historic building area can be interpreted as an area with a close relationship with something past life for moore than 50 years. It can be used collectively in buildings, settlements, and other public facilities. Paper type: Research paper